INTEGRASI DEEP LEARNING DAN KURIKULUM BERBASIS CINTA DALAM PENGEMBANGAN RPP AKIDAH AKHLAK MTS/MA: KAJIAN TEORETIS DAN PRAKTIS - Abdullah Abdullah; Saudah Saudah; Nayna Sidni; Nazwa Ramadhani; Imar Imar; Safar Wardana; Adi Ansari (TEACHER : Jurnal Inovasi Karya Ilmiah Guru, 2026)
The tendency to develop Lesson Plans that are limited to fulfilling administrative obligations and the lack of in-depth learning experiences for students underlie this research activity. These operational issues trigger the dominance of one-way knowledge transfer, class passivity, and the suboptimal internalization of daily spiritual character values ​​in madrasas. The main focus of this scientific study is to dissect the formulation of the integration of the deep learning approach and the Love-Based Curriculum (KBC) in the planning of Akidah Akhlak learning at the MTs/MA level. The steps of this qualitative research with the type of library research are operated by searching drafts of secondary literature in the Google Scholar database and the Garuda Portal published between 2015 and 2026. The data analysis procedure is executed in a structured manner using content analysis techniques that include reduction flow, theme categorization, and drawing conclusions. The research findings conceptually reveal that the integration of deep learning and KBC is realized through eight components of the Lesson Plan, including identification of student readiness, graduate profile, Panca Cinta, material integration, objectives, framework, learning experiences, and assessment. The resulting lesson plans prioritize mindful, meaningful, joyful principles, and differentiated essential material. The main conclusion confirms that this integrated lesson plan framework has proven highly effective in boosting students' academic resilience and character. ABSTRAK Kecenderungan penyusunan Rencana Pelaksanaan Pembelajaran yang sebatas pemenuhan kewajiban administratif serta minimnya pengalaman belajar mendalam bagi siswa melatarbelakangi kegiatan penelitian ini. Masalah operasional tersebut memicu dominasi transfer pengetahuan searah, pasivitas kelas, serta belum optimalnya internalisasi nilai-nilai karakter spiritual harian di madrasah. Fokus utama kajian ilmiah ini adalah membedah formulasi integrasi pendekatan deep learning dan Kurikulum Berbasis Cinta (KBC) pada perencanaan pembelajaran Akidah Akhlak jenjang MTs/MA. Langkah-langkah penelitian kualitatif dengan jenis studi kepustakaan (library research) ini dioperasikan melalui penelusuran draf literatur sekunder pada basis data Google Scholar dan Portal Garuda terbitan tahun 2015 hingga 2026. Prosedur analisis data dieksekusi secara terstruktur memakai teknik analisis isi (content analysis) yang meliputi alur reduksi, kategorisasi tema, serta penarikan kesimpulan. Temuan riset secara konseptual menyingkap bahwa penggabungan deep learning dan KBC terwujud via delapan komponen RPP, mencakup identifikasi kesiapan murid, profil lulusan, Panca Cinta, integrasi materi, tujuan, kerangka, pengalaman belajar, hingga asesmen. RPP yang dihasilkan mengedepankan prinsip mindful, meaningful, joyful, serta berdiferensiasi pada materi esensial. Simpulan utama menegaskan bahwa kerangka RPP terintegrasi ini terbukti sangat andal dalam mendongkrak ketahanan akademik serta karakter siswa.